Cognitive strategies used in the verbal fluency test by elderly in Sergipe's countryside (Bioscience Journal, 2020)
To analyze the cognitive strategies used in the verbal fluency test by healthy elderly without current risk of dementia. Method: Participants of the study were active elderly people, living in the countryside of the state of Sergipe, of both sexes. General identification data and health conditions were collected and the Mental State Mini Exam (MSME) and Verbal Fluency Semantics (VFS) test was applied. People with scores below the cut grade for schooling regarding the MSME were excluded from the survey. The results of these tests were analyzed qualitatively (normal or altered) and quantitatively (general score). In the VFS, the analysis was also performed according to the strategies used by the participant to recall the words (number of categories of animals cited, number of clusters performed (Clustering) and number of exchanges of cognitive strategy (Switching). The results were statistically analyzed by the Pearson correlation test. 33 elderly (25 females and 8 males) participated, with a mean age of 71.6 years old. The mean score in the MSME was 23.6 points and in the VFS it was 12.78 points, with a mean number of category used of 2.9, Clustering of 1.8 and Switching of 1.3. Pearson's correlation test identified important correlations between the VFS results and the number of the animals cited, Clustering and Switching categories used by the participants. Conclusion: Good general cognitive performance and language seems to be related to the cognitive strategies used in VFS, evidencing the importance of using this test in cognitive screening, even in cases of active elderly people.